(untitled) (American International Journal of Education and Linguistics Research, 2019)
Speaking is considered as one of the most important skill in learning a language especially English but many language learners find it difficult and need much effort to produce acceptable utterances in English. The aim of this study is to investigate Psychological factors that become obstacles to spoken English among Malaysian primary school pupils, and suggest possible solutions from the student’s perspectives to overcome the obstacles. For conducting current research, a questionnaire was used to collect data and identify the factors that affect students speaking performance, and find out possible solution from the students’ perspectives. After the data analysed, it was noticed that majority of students were the victims of the common physiological factors such as fear in the class, shyness and anxiety. Most pupils did not have confident to speak because they felt fear to speak in English. While some other were felling shy and anxious when speaking in the class. Thus, pupils suggested solutions like interesting activities, encouraging learning atmosphere, a good rapport between teacher and students to help them to overcome these psychological factors that hinder them to speak in English.